Case Report: ALK-rearranged mesenchymal neoplasms with S100 and CD34 co-expression: additional cases with distinct characteristics - Ouyang, Qi; Guo, Xiaohong; Mao, Rongjun; Cao, Zhixing (Frontiers in Oncology, 2025)
ALK rearrangements are rarely documented in superficial soft tissue neoplasms exhibiting an infantile fibrosarcoma-like spindle cell tumor (IFS) pattern or stromal, resembling Neurotrophic Tyrosine Kinase Receptor(NTRK)rearranged spindle cell tumors. Here, we present two cases of pediatric cutaneous soft tissue tumors with an IFS pattern, in which ALK fusions involving related partner genes were identified. The tumors in both cases demonstrated similar morphology and consisted of ovoid and spindle cells with infiltrative boundaries. The spindle cells exhibited either a fascicular growth pattern or a haphazard pattern and stromal hyalinization. Both cases involved inflammatory cell infiltration, brisk mitosis, and CD34, S100, and ALK-D5F3 immunoreactivity. Next-generation sequencing identified ALK fusion with different partner genes (STRN and PLEKHH2). The fluorescence in situ hybridization break-apart assay confirmed ALK rearrangements in both cases. In case 1, no indications of disease progression or metastasis was observed within the limited follow-up (36 months). However, the patient in case 2 experienced a rapid recurrence and metastasis.